MODEL PEMBELAJARAN MENULIS KARYA ILMIAH: ANALISIS KEBUTUHAN - Hamsa, Akmal; Haliq, Abdul (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2023)
This research aims to describe students' needs for independent learning based on digital literacyin scientific writing courses. This research approach is a mixed approach that combines quantitativemethods and qualitative methods. The data collection techniques used in this research were throughquestionnaires, interviews and documentation studies. This research was conducted on students who weregoing to take a scientific paper writing course. The number of subjects in this research was 100 studentsand 1 lecturer. The research results show that (1) Learning to write scientific papers is one of the coursesin the group of creative skills courses. (2) The course on writing scientific papers is taught in the fourthsemester with a credit load of 3 with the aim of making students understand the various theories of writingscientific papers and being able to apply them in preparing scientific papers. (3) Learning to writescientific papers is ideally carried out using an independent learning model. (4) Use of various kinds ofeasily accessible references such as e-books and online journals which really support independent learningin learning to write scientific papers. (5) Learning to write